Application of Scoring System Components in Children Diagnosed with Tuberculosis in Jatinangor Primary Health Care, Sumedang - Nurwanti, Mutiara Azhara; Chrysanti, Chrysanti; Sudarwati, Sri (Althea Medical Journal, 2017)
Background: Diagnosis of tuberculosis in children is very difficult. Scoring system is used to diagnose tuberculosis in children in Indonesia. The aim of this study was to determine the application of scoring system components in children diagnosed with tuberculosis in the primary health care.Methods: This cross-sectional study was conducted inÂ  Jatinangor Primary Health Care, Sumedang in SeptemberâOctober 2013. Data were obtained from 59 medical records of pediatric patients diagnosed with tuberculosis in 2010â2012, and recorded on the application of scoring system components including tuberculosis contact history, tuberculin skin test, fever, cough, nutritional status, lymph node enlargement, swelling of bones or joints, and chest X-ray. Results: All scoring system components either with tuberculosis contact history, fever, cough, nutritional status, lymph node enlargement, swelling of bones or joints, and chest X-ray were performed on all of the children diagnosed with tuberculosis, except the tuberculin skin test was performed only on 38 (64%) children. Most frequent clinical symptoms were cough (97%), while fever and malnutrition occurred in 69% and 19% of children, respectively.Conclusions: The application of scoring system components in children diagnosed with tuberculosis in Jatinangor primary health care is not having problems, except for the tuberculosis skin test. Most frequent clinical symptoms of childhood tuberculosis in this study are cough.